Positive electrode lithium supplement additive, preparation method thereof, positive plate and lithium ion battery

By using a positive electrode lithium supplement additive with a clad structure in the positive electrode sheet of a lithium-ion battery, the problem of poor positive electrode lithium supplementation effect in the prior art is solved, and the first effect, capacity and cycle stability of the lithium-ion battery are significantly improved.

CN119864381APending Publication Date: 2025-04-22JIANGSU HIGHSTAR BATTERY MFG CO LTD +2

Patent Information

Application Number
CN202311365484.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The positive electrode supplementation effect of existing lithium-ion batteries is poor, resulting in poor first-term effect, capacity and cycle stability of lithium-ion batteries.

Method used

A positive electrode lithium supplement additive is used, which includes a lithium-containing compound, and is coated in a first cladding layer such as aluminum titanium lithium phosphate, lithium lanthanum zirconium oxygen or lithium lanthanum titanium oxygen, and a second cladding layer containing metal compounds such as Ga, Sm, Si, etc.

Benefits of technology

The first cladding layer improves the air stability of the lithium source and process processing stability, prevents the infiltration of electrolyte and prevents side reactions; the second cladding layer provides a smooth channel for lithium ions, reduces battery impedance, and improves capacity and cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004504154060000201
    Figure BDA0004504154060000201
  • Figure BDA0004504154060000211
    Figure BDA0004504154060000211
Patent Text Reader

Abstract

The invention relates to the field of lithium ion batteries, and discloses a positive electrode lithium supplement additive, a preparation method thereof, a positive plate and a lithium ion battery. The lithium supplement additive for the positive electrode comprises a lithium-containing compound, and a first coating layer and a second coating layer which sequentially coat the surface of the lithium-containing compound, wherein the first coating layer comprises at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide and lithium lanthanum titanium oxide; the second coating layer includes at least one of a Ga-containing compound, a Sm-containing compound, a Si-containing compound, an Al-containing compound, a V-containing compound, a Nb-containing compound, a Mg-containing compound, a Zr-containing compound, and a Zn-containing compound. The first coating layer improves the stability in the processing process, prevents side reaction, ensures the structural stability of the positive electrode lithium supplement additive, and improves the cycle performance of the battery; and the second coating layer provides an effective smooth channel for lithium ions, so that the impedance of the battery can be effectively reduced, and the capacity and the cycle performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lithium ion batteries, and in particular to a positive electrode lithium supplement additive and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art

[0002] As people pay more and more attention to environmental protection, nickel-cadmium batteries that bring heavy metal cadmium pollution are subject to more and more restrictions. Nickel-hydrogen batteries have low energy density, short service life, memory effect characteristics and high manufacturing costs, which limit their application. Lithium-ion batteries have excellent performance, high energy density, long cycle life and other advantages, and have been widely used in digital, power tools and other fields. In recent years, the application of electric vehicles and energy storage has developed rapidly, and the development of lithium-ion batteries with long cycle life has become an important topic at present. During the normal use of lithium-ion batteries, active lithium will continue to be consumed, resulting in a reduction in cycle life.

[0003] In response to the phenomenon that the negative electrode SEI film of lithium-ion batteries consumes active lithium, resulting in a reduction in battery life, the solution is to use lithium replenishment technology to supplement the lithium consumption during the cycle, increase the battery capacity and achieve a longer cycle life. At present, lithium replenishment technology mainly uses two methods, one is negative electrode lithium replenishment, and the other is positive electrode lithium replenishment. Negative electrode lithium replenishment is mainly through pole piece metal lithium replenishment or material-side chemical lithium replenishment. Negative electrode lithium replenishment at the pole piece end involves the use of flammable and explosive metallic lithium, which has high safety risks, is more dangerous in industrialization, and has a high degree of operational difficulty; while the chemical lithium replenishment method at the material end is complex, and the material is highly alkaline, making it difficult to process the material. In general, negative terminal lithium replenishment has greater safety risks and complex and difficult processing technology problems. However, the effect of positive terminal lithium replenishment is not good, and the initial efficiency, capacity and cycle stability of lithium-ion batteries need to be improved.

[0004] Therefore, there is an urgent need for a positive electrode lithium replenishing additive added to the positive electrode sheet, which can avoid the safety and operability problems caused by negative terminal lithium replenishment and can improve the initial efficiency, capacity and cycle stability of lithium-ion batteries. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of poor lithium replenishment effect of the positive electrode in the prior art, poor initial efficiency, capacity and cycle stability of lithium-ion batteries, and to provide a positive electrode lithium replenishment additive and a preparation method thereof, a positive electrode sheet and a lithium-ion battery.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a positive electrode lithium supplement additive, wherein the positive electrode lithium supplement additive comprises: a lithium-containing compound, and a first coating layer and a second coating layer sequentially coated on the surface of the lithium-containing compound; wherein,

[0007] The first coating layer includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide and lithium lanthanum titanium oxide;

[0008] The second cladding layer metal includes at least one of a Ga-containing compound, an Sm-containing compound, an Si-containing compound, an Al-containing compound, a V-containing compound, an Nb-containing compound, an Mg-containing compound, a Zr-containing compound, and a Zn-containing compound.

[0009] A second aspect of the present invention provides a method for preparing a positive electrode lithium supplement additive, wherein the preparation method comprises the following steps:

[0010] S1, performing a first mixing of the lithium-containing compound and the first coating material, and then performing a first calcination of the material obtained by the first mixing to obtain a first coating precursor;

[0011] S2, performing a second mixing of the first coating precursor and the second coating material, and then performing a second calcination of the material obtained by the second mixing; wherein,

[0012] The first coating material includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide and lithium lanthanum titanium oxide;

[0013] The second coating material includes at least one of a Ga-containing compound, an Sm-containing compound, a Si-containing compound, an Al-containing compound, a V-containing compound, a Nb-containing compound, a Mg-containing compound, a Zr-containing compound, and a Zn-containing compound.

[0014] The third aspect of the present invention provides a positive electrode lithium supplement additive prepared by the preparation method provided by the present invention.

[0015] A fourth aspect of the present invention provides a positive electrode sheet, wherein the positive electrode sheet is obtained by coating a slurry on the surface of a positive electrode current collector; wherein the slurry includes the positive electrode lithium supplement additive provided by the present invention.

[0016] A fifth aspect of the present invention provides a lithium-ion battery, wherein the battery comprises the positive electrode sheet provided by the present invention.

[0017] Through the above technical solution, the beneficial effects of the present invention at least include:

[0018] The wrapping of the first coating layer (at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide and lithium lanthanum titanium oxide) ensures the air stability of the lithium source, improves the stability during the process, and at the same time prevents the infiltration of electrolyte in the later stage of the battery cycle, prevents the occurrence of side reactions, ensures the structural stability of the positive electrode lithium supplement additive, and improves the battery's cycle performance; the second coating layer provides an effective and unobstructed channel for lithium ions, which can effectively reduce the battery impedance and improve the battery's capacity and cycle performance.

[0019] In a preferred embodiment of the present invention, by selecting a suitable amount of the positive electrode lithium supplement additive, the average pore size and porosity of the first coating material lithium carbonate when preparing the positive electrode lithium supplement additive, the type and amount of the second coating material, and the calcination temperature during the first layer coating and the second layer coating, the battery's first formation efficiency, volumetric capacity and battery cycle performance are further improved. DETAILED DESCRIPTION

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0021] The first aspect of the present invention provides a positive electrode lithium supplement additive, wherein the positive electrode lithium supplement additive comprises: a lithium-containing compound, and a first coating layer and a second coating layer sequentially coated on the surface of the lithium-containing compound; wherein,

[0022] The first coating layer includes at least one of lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO) and lithium lanthanum titanium oxide (LLTO);

[0023] The second cladding layer includes at least one of a Ga-containing compound, an Sm-containing compound, an Si-containing compound, an Al-containing compound, a V-containing compound, a Nb-containing compound, a Mg-containing compound, a Zr-containing compound, and a Zn-containing compound.

[0024] The wrapping of the first coating layer ensures the air stability of the lithium source and improves the stability during the process. At the same time, it prevents the infiltration of electrolyte in the later stage of the battery cycle, prevents the occurrence of side reactions, ensures the structural stability of the positive electrode lithium supplement, and improves the battery's cycle performance; the second coating layer provides an effective and unobstructed channel for lithium ions, which can effectively reduce the battery impedance and improve the battery's capacity and cycle performance.

[0025] According to the present invention, preferably, based on the total weight of the positive electrode lithium replenishing additive, the contents of the lithium-containing compound, the first coating layer and the second coating layer in the positive electrode lithium replenishing additive are 80-99.8wt%, 0.01-20wt% and 0.01-20wt% respectively.

[0026] According to the present invention, preferably, the lithium-containing compound is selected from at least one of lithium acetate, lithium carbonate, lithium hydroxide and lithium nitrate, preferably lithium carbonate.

[0027] In order to reduce the battery impedance and improve the battery capacity and cycle performance, the surface of the positive electrode lithium supplement additive also has a second coating layer. Preferably, the Ga-containing compound is selected from at least one of gallium phosphide, gallium antimonide, gallium telluride and gallium nitrate;

[0028] and / or, the Sm-containing compound is selected from at least one of samarium oxide, samarium sulfide and samarium telluride;

[0029] And / or, the Si-containing compound is selected from at least one of silicon oxide, silicon sulfide and silicon chloride;

[0030] And / or, the Al-containing compound is selected from at least one of aluminum oxide, aluminum hydroxide and aluminum carbonate;

[0031] And / or, the V-containing compound is selected from at least one of vanadium oxide, vanadate and vanadium oxyhalide;

[0032] and / or, the Nb-containing compound is selected from at least one of niobium oxide, lithium niobate and niobium sulfide;

[0033] And / or, the Mg-containing compound is selected from at least one of magnesium oxide, magnesium hydroxide and magnesium nitride;

[0034] and / or, the Zr-containing compound is selected from at least one of zirconium dioxide, zirconium acetate and zirconium disilicide;

[0035] And / or, the Zn-containing compound is at least one selected from zinc oxide, zinc chloride and zinc fluoride.

[0036] Furthermore, the second coating layer is an Al-containing compound, more preferably aluminum oxide.

[0037] A second aspect of the present invention provides a method for preparing a positive electrode lithium supplement additive, wherein the preparation method comprises the following steps:

[0038] S1, performing a first mixing of the lithium-containing compound and the first coating material, and then performing a first calcination of the material obtained by the first mixing to obtain a first coating precursor;

[0039] S2, performing a second mixing of the first coating precursor and the second coating material, and then performing a second calcination of the material obtained by the second mixing; wherein,

[0040] The first coating material includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide and lithium lanthanum titanium oxide;

[0041] The second coating material includes at least one of a Ga-containing compound, an Sm-containing compound, a Si-containing compound, an Al-containing compound, a V-containing compound, a Nb-containing compound, a Mg-containing compound, a Zr-containing compound, and a Zn-containing compound.

[0042] The types of the lithium-containing compound, the first coating material and the second coating material described in the preparation method of the positive electrode lithium replenishing additive in the second aspect of the present invention are the same as the types of the lithium-containing compound, the first coating layer and the first coating layer described in the positive electrode lithium replenishing additive in the first aspect of the present invention, and will not be repeated in the second aspect of the present invention.

[0043] The lithium-containing compound in the positive electrode lithium supplement additive is a porous nanostructure, which provides an effective and smooth channel for lithium ions, can effectively reduce battery impedance, and improve battery capacity and cycle performance. Preferably, the average pore size of the lithium-containing compound is 5-200nm, preferably 100-150nm; the porosity is 0.2-48%, preferably 20-40%.

[0044] In order to further improve the structural stability of the positive electrode lithium supplement additive and further improve the cycle performance of the battery, preferably, in S1, the lithium-containing compound and the first coating material are first mixed in a weight ratio of 1: (0.0001-0.25).

[0045] In order to further improve the coating effect of the first coating material, make the first coating layer more evenly distributed on the lithium-containing compound and the coating more firmly, preferably, the first mixing is carried out in the presence of a first solvent.

[0046] Preferably, the first solvent is selected from C1-C4 monohydric alcohols, preferably ethanol.

[0047] Preferably, based on the total weight of the lithium-containing compound and the first coating material being 1 g, the amount of the first solvent used is 0.5-20 mL, preferably 1.5-2.5 mL.

[0048] Preferably, the temperature of the first mixing is 20-30° C., and the time is 10-30 min.

[0049] The first mixing is performed in the presence of a first solvent, and in order to obtain a dried first coating precursor solid, the first solvent is removed after the first mixing. The present invention does not particularly limit the method for removing the first solvent, and in a preferred case, the first solvent is removed by evaporation, and the method for removing the first solvent comprises: stirring the liquid material after the first mixing at 55-65° C., thereby evaporating the first solvent.

[0050] In order to further improve the firmness of the first coating material on the lithium-containing compound, preferably, the first calcination temperature is 400-1000°C, preferably 600-1000°C; the time is 60-900min, preferably 400-900min.

[0051] In order to further enhance the effect of the positive electrode lithium supplement additive on improving the capacity and cycle performance of the battery, preferably, in S2, the first coating precursor and the second coating material are mixed in a weight ratio of 100: (0.01-25).

[0052] In order to further improve the coating effect of the second coating material and make the second coating material more evenly distributed on the first coating precursor and more firmly coated, preferably, the second mixing is carried out in the presence of a second solvent; and / or the second mixing is carried out at 30-80°C.

[0053] Furthermore, the second mixing is performed in a reflux manner, preferably at a reflux temperature, and the reflux time is 25-40 min.

[0054] According to the present invention, preferably, the second solvent is selected from C1-C4 monohydric alcohols, preferably at least one of ethanol, methanol and isopropanol.

[0055] According to the present invention, preferably, based on the total weight of the first coating precursor and the second coating material being 1 g, the amount of the second solvent used is 0.5-20 mL, preferably 1.5-3.5 mL.

[0056] The second mixing is performed in the presence of a second solvent. In order to facilitate the second calcination and obtain a positive electrode lithium supplement additive with good structure and performance, the second solvent is removed after the second mixing. The present invention does not particularly limit the method for removing the second solvent. In a preferred case, the second solvent is removed by suction filtration.

[0057] In order to further remove the second solvent, the filtrate is dried after filtration, for example, vacuum drying can be performed at 70-100°C.

[0058] In order to further improve the firmness of the second coating material on the first coating precursor, preferably, the second calcination temperature is 400-700° C. and the time is 200-480 min.

[0059] In order to prepare slurry by adding to the positive electrode material with a more suitable particle size, preferably, the product after the second calcination is further cooled, crushed, screened and demagnetized, and screened with a 150-250 mesh screen to obtain a positive electrode lithium supplement additive with uniform particles.

[0060] According to a preferred embodiment of the present invention, the preparation method of the positive electrode lithium supplement additive comprises the following steps:

[0061] S1. Add the lithium-containing compound into a container with a stirring device, add ethanol solution, and stir continuously for 10min-30min to disperse the lithium-containing compound in the solution; then add the first coating material according to the weight ratio to form a mixed solution, and stir the mixed solution continuously for 10min-30min; after stirring, transfer to a water bath pot with a stirring device, continue stirring and heating at 55-65℃, and after the solvent is evaporated, transfer the obtained powder to a porcelain boat, and roast it continuously at 400℃-1000℃ for 60min-900min in an air atmosphere to obtain a first coating precursor.

[0062] S2. Dissolve the second coating material in the second solvent, then add the first coating precursor, stir and heat to reflux, reflux for 25-40 minutes, remove the second solvent by suction, and vacuum dry at 70-100°C to obtain a semi-finished product; place the semi-finished product in a muffle furnace, roast at 400-700°C for 200-480 minutes, and naturally cool to room temperature to obtain a positive electrode lithium supplement additive.

[0063] In the present invention, lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO) and lithium lanthanum titanium oxide (LLTO) can be obtained commercially or homemade. Lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO) and lithium lanthanum titanium oxide (LLTO) can be prepared by the following method:

[0064] Preparation of LATP by coprecipitation method: Lithium nitrate (LiNO3) and aluminum nitrate (Al(NO3)3) in a stoichiometric ratio were dissolved in an appropriate amount of distilled water, and the mixed solution was stirred until it was clear and transparent. 16 H 36 O4Ti) is dissolved in an appropriate amount of anhydrous ethanol, and then slowly added to the above mixed solution, and then an excess of precipitant is added. Finally, ammonium dihydrogen phosphate (NH4H2PO4) is dissolved in an appropriate amount of distilled water and slowly added to the above mixed solution. The mixed solution is reacted, aged, washed with water, and washed with alcohol at a certain temperature to obtain a white precipitate. The white precipitate is dried to obtain a LATP precursor, and the precursor is calcined in an air atmosphere at 400-1000℃, and naturally cooled to obtain LATP powder.

[0065] Preparation of LLZO by sol-gel method: LiNO3, La(NO3)3 and keto acid zirconium in stoichiometric amounts with 1wt% additional Li source are dissolved in water to obtain a stable sol. After the salt is completely dissolved, citric acid and ethylenediaminetetraacetic acid (EDTA) are added to the water. The pH value is adjusted to 6.5 by ammonium hydroxide to completely dissolve EDTA. The solution is stirred at 65-75°C while evaporating the solvent therein to produce a gel, which is then maintained at 275-285°C for 2-3 hours and calcined at 870-930°C for 3-5 hours. High-purity nano LLZO powder is obtained after ball milling.

[0066] Preparation of LLTO: Lithium nitrate and lanthanum nitrate that meet the stoichiometric amount are dissolved in ethanol to obtain a mixed solution A, acetylacetone is added to tetrabutyl titanate and stirred evenly to obtain a mixed solution B; the mixed solution A and the mixed solution B are adjusted to control the pH value to 0.25-1 with deionized water and acetic acid respectively, mixed and stirred to obtain a clear and transparent sol solution; the above sol solution is placed in an oven to dry to obtain a fluffy dry powder; the above dry powder is ground and placed in a muffle furnace to calcine at 800-900°C for 1.5-2.5 hours to obtain pure LLTO.

[0067] The third aspect of the present invention provides a positive electrode lithium supplement additive prepared by the preparation method provided by the present invention.

[0068] The fourth aspect of the present invention provides a positive electrode sheet, wherein the positive electrode sheet is obtained by coating a positive electrode slurry on the surface of a positive electrode current collector; wherein the positive electrode slurry includes the positive electrode lithium replenishing additive provided by the present invention. The positive electrode lithium replenishing additive provided by the present invention can be used for positive electrode materials of various lithium-ion batteries to play a role in replenishing lithium.

[0069] According to the present invention, the positive electrode slurry further comprises a positive electrode active material, a positive electrode conductive agent, a positive electrode binder and a solvent, wherein the positive electrode lithium supplement additive, the positive electrode active material, the positive electrode conductive agent and the positive electrode binder constitute a positive electrode powder.

[0070] According to the present invention, preferably, the weight ratio of the positive electrode lithium replenishing additive, the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is (1-10):96:(1-5):(0.5-2.5), preferably (2-4):96:(1-5):(0.5-2.5). The content of the positive electrode lithium replenishing additive directly affects the lithium replenishing effect. If the content is too small, it is not enough to play a role in improving the electrical performance of the battery. If the content is too high, it is not conducive to the gram capacity and the first effect of the positive electrode. Among them, the amount of positive electrode binder is measured in solid amount.

[0071] The present invention has no particular restrictions on the type of solvent in the positive electrode slurry, and can be a conventional solvent used in the art for preparing positive electrode slurries, such as N-methylpyrrolidone (NMP), and the content of the solvent in the positive electrode slurry can be 25-35wt%, that is, the solid content (total powder content) is 65-75wt%. When the solid content is within this range, the positive electrode slurry has a suitable viscosity, which is conducive to the subsequent coating of the slurry.

[0072] The present invention has no particular limitation on the type of the positive electrode current collector, which may be a conventional positive electrode current collector in the art. Preferably, the positive electrode current collector is aluminum foil.

[0073] The present invention has no particular restriction on the type of positive electrode active material, which may be a conventional positive electrode active material in the art. For example, the positive electrode active material may be selected from at least one of lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiMPO4) and lithium nickel cobalt manganese oxide, preferably at least one of lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4) and lithium iron phosphate (LiMPO4); wherein LiMn2O4 is a spinel type and LiMPO4 is an olivine type.

[0074] The present invention has no particular limitation on the type of the positive electrode conductive agent, which may be any conventional material in the art for positive electrode conductive properties. For example, the positive electrode conductive agent may be selected from at least one of conductive carbon black (SP), carbon fiber, acetylene black, Ketjen black, graphene and carbon nanotubes (CNTs).

[0075] The present invention has no particular restrictions on the type of positive electrode binder, and can be a material conventionally used in the field for positive electrodes and capable of bonding positive electrode materials to each other. For example, the positive electrode binder can be selected from at least one of polypropylene, polyethylene, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene and polyhexafluoropropylene. The present invention has no particular restrictions on the weight average molecular weight of the aforementioned polymer, as long as it can meet the requirements of being a binder. For example, the positive electrode binder can be selected from the aforementioned polymer having a weight average molecular weight of 8000-10000 g / mol.

[0076] A fifth aspect of the present invention provides a lithium-ion battery, wherein the battery comprises the positive electrode sheet provided by the present invention.

[0077] According to the present invention, the battery further comprises a negative electrode sheet, a separator and an electrolyte.

[0078] According to the present invention, the negative electrode sheet is obtained by coating the negative electrode slurry on the surface of the negative electrode current collector. The negative electrode slurry also includes a negative electrode active material, a negative electrode conductive agent, a negative electrode binder and a solvent. Among them, the combination of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder constitutes a negative electrode powder.

[0079] According to the present invention, preferably, the weight ratio of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder is (90-100): (1-2): (1-5), wherein the amount of the negative electrode binder is calculated as solid amount.

[0080] The present invention has no particular restrictions on the type of solvent in the negative electrode slurry, and can be a conventional solvent used in the art for preparing the negative electrode slurry, such as water, and the content of the solvent in the negative electrode slurry can be 50-65wt%, that is, the solid content is 35-50wt%. When the solid content is within this range, the negative electrode slurry has a suitable viscosity, which is conducive to the subsequent coating of the slurry.

[0081] The present invention has no particular limitation on the type of the negative electrode current collector, which may be any conventional negative electrode current collector in the art. Preferably, the negative electrode current collector is copper foil.

[0082] The present invention has no particular limitation on the type of negative electrode active material, which may be conventional negative electrode active materials in the art. For example, the negative electrode active material may be selected from a combination of one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microbeads, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium.

[0083] The present invention has no particular limitation on the type of the negative electrode conductive agent, which may be any conventional material in the art for negative electrode conductive properties. For example, the negative electrode conductive agent may be selected from at least one of conductive carbon black, carbon fiber, acetylene black, Ketjen black, graphene and carbon nanotubes.

[0084] The present invention has no particular restrictions on the type of negative electrode binder, and can be a material conventionally used in the art for negative electrodes and capable of bonding negative electrode materials to each other. For example, the negative electrode binder can be selected from at least one of polypropylene, polyethylene, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene, and polyhexafluoropropylene. The present invention has no particular restrictions on the weight average molecular weight of the aforementioned polymer, as long as it can meet the requirements of being a binder. For example, the negative electrode binder can be selected from the aforementioned polymer having a weight average molecular weight of 1000-100000 g / mol.

[0085] The present invention has no particular limitation on the type of the diaphragm, and it can be any material suitable for lithium-ion battery separators in the art. For example, the diaphragm can be selected from at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.

[0086] The present invention has no particular restrictions on the composition of the electrolyte. The electrolyte included in the electrolyte can be various electrolytes suitable for lithium-ion batteries in the art. For example, the electrolyte can generally include lithium salts, etc. More specifically, the lithium salts can be inorganic lithium salts and / or organic lithium salts, etc. Specifically, it can include but is not limited to lithium salts selected from at least one of LiPF6, LiBF4, LiN(SO2F)2 (abbreviated as LiFSI), LiN(CF3SO2)2 (abbreviated as LiTFSI), LiClO4, LiAsF6, LiB(C2O4)2 (abbreviated as LiBOB), and LiBF2C2O4 (abbreviated as LiDFOB). For another example, the concentration of the electrolyte can be 0.8-1.5 mol / L.

[0087] According to the present invention, the electrolyte may further include additives, which may be negative electrode film-forming additives (e.g., vinyl sulfite, lithium bis(oxalate borate), etc.), or positive electrode film-forming additives (e.g., tris(trifluoromethyl)phosphine, sulfonate, etc.), and may further include additives capable of improving certain properties of lithium-ion batteries, such as additives for improving battery cycle performance (e.g., hydroquinone difluorosulfonate, methylene disulfonate, 1,3,5-triallyl isocyanurate, etc.), additives for improving battery overcharge performance (e.g., vinyl disulfate, propylene sulfite, triallyl phosphate, etc.), additives for improving battery high temperature performance (e.g., vinyl carbonate, vinyl ethylene carbonate, propylene carbonate), etc.

[0088] According to a specific embodiment of the present invention, the method for preparing the lithium ion battery comprises the following steps:

[0089] (1) Preparation of positive electrode sheet: Add positive electrode binder to solvent to prepare positive electrode glue with solid content of 6-9wt%, then add positive electrode conductive agent, positive electrode active material, and positive electrode lithium supplement dissolved in solvent to the glue, stir until uniformly dispersed, add solvent to adjust the solid content of slurry to 65-75wt%, and obtain positive electrode slurry. Coat the positive electrode slurry on the positive electrode current collector, then roll and cut into strips to obtain positive electrode sheet;

[0090] (2) preparing a negative electrode sheet: adding a negative electrode binder to a solvent to prepare a negative electrode glue having a solid content of 6-9 wt%, then adding a negative electrode conductive agent and a negative electrode active material, and then adding a solvent to adjust the solid content of the slurry to 35-50 wt% to obtain a negative electrode slurry, coating the negative electrode slurry on a negative electrode current collector, and then rolling and slitting to obtain a negative electrode sheet;

[0091] (3) winding, assembling and injecting the positive electrode sheet, the negative electrode sheet, the separator and the electrolyte to obtain a battery to be formed;

[0092] (4) The battery to be formed is subjected to formation and aging in sequence to obtain the soft-pack lithium-ion battery.

[0093] Wherein, the solvent in step (1) is N-methylpyrrolidone (NMP), and the solvent in step (2) is water.

[0094] The conditions for the formation in step (4) include: (a) 0.05-0.1C constant current charging for 0.5-1h, to a cut-off voltage of 3.3-3.6V; (b) 0.08-0.15C constant current charging for 0.5-1h, to a cut-off voltage of 3.3-3.6V; (c) 0.16-0.2C constant current charging for 0.8-1.2h, to a cut-off voltage of 3.3-3.6V; (d) 0.2-0.3C constant current constant voltage charging for 3.5-4.5h, to a cut-off voltage of 4.15-4.35V, a cut-off current of 0.02C-0.05C; (e) 0.2-0.5C constant current discharge for 3-5h, to a cut-off voltage of 2.0-2.75V. In the present invention, unless otherwise specified, room temperature refers to 23±2°C.

[0095] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples, unless otherwise specified, all are conventional methods; the reagents and materials used, unless otherwise specified, can be obtained from commercial channels. The determination methods involved in each example and comparative example are as follows:

[0096] The first formation effect of the battery under 0.2C conditions was tested using the BTS series battery test cabinet of Shenzhen Xinwei Electronics Co., Ltd. The specific test method is as follows: (a) 0.2C constant current charging to a cut-off voltage of 4.35V, then switching to 4.35V constant voltage charging to a cut-off current of 0.02C; (b) leaving for 30 minutes; (c) 0.2C constant current discharge to 2.5V. The ratio of the discharge capacity in step (c) to the charge capacity in step (a) is the first formation effect.

[0097] The capacity of the battery is tested using the BTS series battery test cabinet of Shenzhen Xinwei Electronics Co., Ltd. The specific test method is as follows: (a) 0.5C constant current charging to a cut-off voltage of 3.65V, then 3.65V constant voltage charging to a cut-off current of 0.05C; (b) standby for 30 minutes; (c) 0.5C constant current discharge to 2.5V. The discharge capacity in step (c) is the capacity of the battery.

[0098] The cycle life data was measured by the BTS series battery test cabinet of Shenzhen Xinwei Electronics Co., Ltd. The specific test method is as follows: (a) 1C constant current charging to a cut-off voltage of 3.65V, then switch to 3.65V constant voltage charging to a cut-off current of 0.05C; (b) stand for 30 minutes; (c) 1C constant current discharge to 2.5V. The discharge capacity of step (c) is the fractional capacity of the battery. Repeat steps (a) to (c) until the capacity is less than 80% of the initial capacity.

[0099] Conductive carbon black (SP) for the positive and negative electrodes was a commercial product of Belgian company Termeco, and carbon nanotubes (CNT) were a commercial product of Jiangsu Tiannai Technology;

[0100] The positive electrode binder polyvinylidene fluoride (PVDF) is a commercial product of Solvay Chemical Company of Belgium, with a weight average molecular weight of 9580 g / mol and a brand number of 5130;

[0101] The negative electrode conductive agent conductive carbon black (SP) is a commercial product of Termeco, Belgium;

[0102] The negative electrode binder modified polyacrylic acid is a commercial product of Shanghai Yanyi, with a weight average molecular weight of 3840 g / mol and a brand name of Sone-PC44S.

[0103] Preparation Example

[0104] This preparation example is used to illustrate the preparation of a lithium-ion battery. The preparation method of the lithium-ion battery is as follows:

[0105] (1) Preparation of positive electrode sheet: Using NMP as solvent, PVDF binder was made into glue with a solid content of 8 wt%, and then positive electrode conductive agent, positive electrode lithium supplement additive and positive electrode active material were added to the glue, and stirred evenly to obtain a slurry with a solid content of 67%. The positive electrode slurry was coated on an aluminum foil with a thickness of 16 μm and a surface density of 118 g / cm 2 , use a double-roller rolling machine to roll the coated and dried positive electrode sheet to a thickness of 119μm, then use a slitting machine to cut the rolled positive electrode sheet, reserve the electrode ear welding position on the positive electrode sheet, and place the cut positive electrode sheet in a high vacuum oven to control the moisture content of the positive electrode sheet to less than 150ppm.

[0106] (2) Preparation of negative electrode sheet: using water as solvent, adding negative electrode binder (modified polyacrylic acid, brand Sone-PC44S) to obtain glue with a solid content of 8 wt%, then adding negative electrode conductive agent SP and negative electrode active material, stirring evenly, to obtain slurry with a solid content of 45%; coating the negative electrode slurry on a copper foil with a thickness of 8 μm, using a double-roll rolling machine to roll the coated and dried negative electrode sheet to a thickness of 80 μm, with a surface density of 54 g / cm 2 Then use a slitting machine to cut the rolled negative electrode sheets, reserve two tab connection positions on the negative electrode sheets, so that the obtained negative electrode sheets are all bipolar tab sheets, and put the cut negative electrode sheets into a high vacuum oven to control the moisture content of the negative electrode sheets to less than 150ppm.

[0107] (3) Preparation of electrolyte: The electrolyte solvent is made of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 2:1:15, and the lithium salt is LiPF6; in the electrolyte, the lithium salt concentration is 1.5 mol / L, and the additives TMSB (trimethylsilyl borate), VC and TMSP (trimethylsilyl phosphate) are made in a weight ratio of 2.5:1:1, and the additive concentration is 1.3-2.8 mol / L.

[0108] (4) Preparation of diaphragm: PP / PE / PP ordinary diaphragm with a thickness of 16 μm was used.

[0109] (5) Assembling batteries: Using a sheet-making and winding machine, the negative electrode sheet, separator, positive electrode sheet, and separator are wound in the order of winding to form a core; then, the core is wound through cold and hot pressing, top sealing, side sealing, corner sealing, and short-circuit testing to obtain a soft-pack battery cell to be filled with liquid; the electrolyte is injected in an environment with a dew point temperature of -45°C, and then the core is vacuum-sealed to form a soft-pack lithium-ion battery.

[0110] (6) Aging, formation and final sealing: The battery after storage is aged and formed in sequence, wherein the aging conditions include: placing the formed battery in a 45°C oven for 24 hours, and the formation conditions include: (a) 0.05C constant current charging for 0.5 hours, to a cut-off voltage of 3.5V; (b) 0.08C constant current charging for 0.5 hours, to a cut-off voltage of 3.6V; (c) 0.2C constant current charging for 1 hour, to a cut-off voltage of 3.65V; (d) 0.25C constant current constant voltage charging for 10 hours, to a cut-off voltage of 4.3V, with a cut-off current of 0.02C; (e) 0.3C constant current discharge for 5 hours, to a cut-off voltage of 2.5V. The finished battery is then vacuum sealed to obtain a finished battery.

[0111] The composition of the positive electrode lithium supplement additive is determined as follows: take 0.5g of sample, accurate to 00.0001g, slowly add 30ml of hydrochloric acid to a 250ml beaker, cover with a watch glass, heat on an electric stove until the sample is completely dissolved, dilute with water and transfer to a 250ml volumetric flask, dilute to volume and shake well. Transfer 10ml to a 100ml volumetric flask, dilute to volume and shake well. Use inductively coupled plasma emission spectrometer ICP-OES for testing.

[0112] Example 1

[0113] The preparation method of the positive electrode lithium supplement additive is as follows:

[0114] S1. Add 100g of lithium-containing compound (lithium carbonate, with an average pore size of 105nm and a porosity of 24.1%) into a container with a stirring device, add 200ml of ethanol solution, and stir continuously for 15min at room temperature to disperse the lithium-containing compound in the solution; then add 2.6g of the first coating material (LATP) to form a mixed solution, and stir the mixed solution continuously at room temperature for 20min; after stirring, transfer to a water bath with a stirring device, and continue stirring and heating at 60°C; after the solvent is evaporated, transfer the obtained powder to a porcelain boat, and calcine continuously at 700°C for 480min in an air atmosphere; after sintering, obtain the lithium-containing compound coated with LATP, i.e., the first coating precursor.

[0115] S2: dissolve 2.7g of alumina in 250mL of ethanol solution as a coating liquid; add 102.6g of the first coating precursor obtained in S1 to the coating liquid, stir and heat to reflux; after refluxing for 30 minutes, filter to remove the solvent, and vacuum dry at 850°C to obtain a semi-finished product; place the semi-finished product in a muffle furnace, roast at 550°C for 340 minutes, and naturally cool to room temperature to obtain a finished positive electrode lithium supplement additive.

[0116] In the positive electrode lithium supplement additive, the contents of the lithium-containing compound, the first coating layer (LATP) and the second coating layer (aluminum oxide) are 95wt%, 2.5wt% and 2.5wt% respectively. The composition of the battery is as follows:

[0117] Positive electrode active material: olivine structured lithium iron phosphate (LiMPO4) material;

[0118] Positive electrode conductive agent: single-walled CNT and SP in a weight ratio of 1:1.2;

[0119] Positive electrode binder: PVDF;

[0120] The weight ratio of the positive electrode lithium supplement additive, the positive electrode active material, the positive electrode conductor and the positive electrode binder is 3:96:2.2:1.8.

[0121] Negative electrode active material: graphite;

[0122] Negative electrode conductive agent: SP;

[0123] Negative electrode binder: modified polyacrylic acid, brand Sone-PC44S;

[0124] The weight ratio of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder is 96:1.5:2.5.

[0125] A lithium ion battery was prepared according to the method of Preparation Example.

[0126] Example 2

[0127] The positive electrode lithium supplement additive and the lithium ion battery are prepared according to the method of Example 1, except that the first coating material is different. Specifically, in S1, the "first coating material (LATP)" of Example 1 is replaced with "first layer coating material (LLZO)". A finished metal positive electrode lithium supplement additive is obtained. Then a lithium ion battery is prepared.

[0128] In the positive electrode lithium supplement additive, the contents of the lithium-containing compound, the first coating layer (LLZO) and the second coating layer (aluminum oxide) are 95wt%, 2.5wt% and 2.5wt% respectively.

[0129] Example 3

[0130] The positive electrode lithium supplement additive and the lithium ion battery were prepared according to the method of Example 1, except that in S1, the "first coating material (LATP)" in Example 1 was replaced by "first coating material (LLTO)". A finished positive electrode lithium supplement additive was obtained. Then, a lithium ion battery was obtained.

[0131] In the positive electrode lithium supplement additive, the contents of the lithium-containing compound, the first coating layer (LLTO) and the second coating layer (aluminum oxide) are 95wt%, 2.5wt% and 2.5wt% respectively.

[0132] Example 4

[0133] A lithium-ion battery was prepared according to the method of Example 1, except that the amount of the positive electrode lithium supplement additive in the positive electrode sheet was different. Specifically, "the weight ratio of the positive electrode lithium supplement additive, the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is 5:96:2.2:1.8" was used to replace "the weight ratio of the positive electrode lithium supplement additive, the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is 3:96:2.2:1.8". A lithium-ion battery was prepared.

[0134] Example 5

[0135] A lithium-ion battery was prepared according to the method of Example 1, except that the amount of the positive electrode lithium supplement additive in the positive electrode sheet was different. Specifically, "the weight ratio of the positive electrode lithium supplement additive, the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is 1:96:2.2:1.8" was used to replace "the weight ratio of the positive electrode lithium supplement additive, the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is 3:96:2.2:1.8". A lithium-ion battery was prepared.

[0136] Example 6

[0137] A lithium-ion battery was prepared according to the method of Example 1, except that the amount of the positive electrode lithium supplement additive in the positive electrode sheet was different. Specifically, "the weight ratio of the positive electrode lithium supplement additive, the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is 3:96:2.2:1.8" was replaced by "the weight ratio of the positive electrode lithium supplement additive, the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is 12:96:2.2:1.8". A lithium-ion battery was prepared.

[0138] Example 7

[0139] A lithium-ion battery was prepared according to the method of Example 1, except that the type of lithium-containing compound was different. Specifically, "lithium-containing compound (lithium carbonate, average pore size of 12 nm, porosity of 15%)" was used to replace "lithium-containing compound (lithium carbonate, average pore size of 105 nm, porosity of 24.1%)". A positive electrode lithium supplement additive was prepared, and then a lithium-ion battery was prepared.

[0140] In the positive electrode lithium supplement additive, the contents of the lithium-containing compound, the first coating layer (LATP) and the second coating layer (aluminum oxide) are 95wt%, 2.5wt% and 2.5wt% respectively.

[0141] Example 8

[0142] A lithium-ion battery was prepared according to the method of Example 1, except that in S1, "500° C. continuous calcination for 240 min" was used instead of "700° C. continuous calcination for 480 min". A positive electrode lithium supplement additive was obtained, and then a lithium-ion battery was obtained.

[0143] In the positive electrode lithium supplement additive, the contents of the lithium-containing compound, the first coating layer (LATP) and the second coating layer (aluminum oxide) are 95wt%, 2.5wt% and 2.5wt% respectively.

[0144] Example 9

[0145] A lithium-ion battery was prepared according to the method of Example 1, except that the amount of the second coating material was different. Specifically, in S2, "2.7 g of aluminum oxide was dissolved in 250 mL of ethanol solution as a coating solution" was replaced by "30 g of aluminum oxide was dissolved in 2500 mL of ethanol solution as a coating solution". A positive electrode lithium supplement additive was obtained, and then a lithium-ion battery was obtained.

[0146] In the positive electrode lithium supplement additive, the contents of the lithium-containing compound, the first coating layer (LATP) and the second coating layer (aluminum oxide) are 75.4wt%, 2wt% and 22.6wt% respectively.

[0147] Example 10

[0148] A lithium-ion battery was prepared according to the method of Example 1, except that the type of the second coating material was different. Specifically, in S2, "2.7 g of zinc oxide" was used to replace "2.7 g of aluminum oxide". A positive electrode lithium supplement additive was prepared, and then a lithium-ion battery was prepared.

[0149] In the positive electrode lithium supplement additive, the contents of the lithium-containing compound, the first coating layer (lithium aluminum titanium phosphate (LATP)) and the second coating layer (zinc oxide) are 95wt%, 2.5wt% and 2.5wt% respectively.

[0150] Embodiment 11

[0151] A lithium-ion battery was prepared according to the method of Example 1, except that in S2, "calcining at 750° C. for 100 min" was used instead of "calcining at 550° C. for 340 min". A positive electrode lithium supplement additive was obtained, and then a lithium-ion battery was obtained.

[0152] In the positive electrode lithium supplement additive, the contents of the lithium-containing compound, the first coating layer (lithium aluminum titanium phosphate (LATP)) and the second coating layer (aluminum oxide) are 95wt%, 2.5wt% and 2.5wt% respectively.

[0153] Comparative Example 1

[0154] A lithium ion battery was prepared according to the method of Example 1, except that no positive electrode lithium supplement additive was added to the positive electrode sheet. A lithium ion battery was prepared.

[0155] Comparative Example 2

[0156] A lithium-ion battery was prepared according to the method of Example 1, except that the positive electrode lithium supplement additive was not subjected to the first layer coating and the second layer coating. That is, lithium carbonate with an average pore size of 105 nm and a porosity of 24.1% was directly added to the battery slurry as the positive electrode lithium supplement additive to prepare a lithium-ion battery.

[0157] Comparative Example 3

[0158] A lithium ion battery was prepared according to the method of Example 1, except that the lithium supplement additive was not double-coated, but lithium carbonate with an average pore size of 105 nm and a porosity of 24.1% was dissolved in ethanol (the total weight of lithium carbonate, LATP and alumina was 1 g, and the amount of ethanol was 2.5 mL) and mixed, and then calcined at 550° C. for 340 min and naturally cooled to room temperature to obtain a positive electrode lithium supplement additive, and then a lithium ion battery was prepared.

[0159] In the positive electrode lithium supplement additive, the contents of the lithium-containing compound, LATP and aluminum oxide are 95wt%, 2.5wt% and 2.5wt% respectively.

[0160] Comparative Example 4

[0161] A lithium-ion battery is prepared according to the method of Example 1, except that the positive electrode lithium supplement additive is not coated with a second layer, that is, the first coated precursor obtained in S1 is used as the positive electrode lithium supplement additive to prepare a lithium-ion battery.

[0162] In the positive electrode lithium supplement additive, the contents of the lithium-containing compound and the first coating layer (LATP) are 96.25wt% and 3.75wt% respectively.

[0163] Test Example 1

[0164] At 23°C, the first formation efficiency and the capacity distribution of the finished batteries prepared in each embodiment and comparative example were tested under 0.2C conditions. The battery was charged with a constant current of 3A at room temperature, and then charged to 3.65V with a constant voltage of 150mA, and then discharged to 2.5V with a constant current of 3A, and the charge and discharge cycle was performed to measure the energy retention rate of the finished batteries prepared in each embodiment and comparative example after 5000 cycles. The finished batteries prepared in each embodiment and comparative example were tested to see whether they caught fire or exploded after being fully charged under the conditions of short circuit and overcharge (after the battery is fully charged, it is charged with a current of 1C until the battery voltage reaches 5.5V or the charging time reaches 60 minutes, and observed for 1 hour (the test is stopped when one of the conditions is met first)). The results are shown in Table 1.

[0165] Table 1

[0166]

[0167]

[0168] It can be seen from the results in Table 1 that the lithium-ion batteries prepared in Examples 1-11 of the present invention have excellent electrochemical properties, high first effect of formation and fractional capacity, and excellent cycle performance and safety performance. No positive electrode lithium supplement additive is added to the positive electrode sheet of Comparative Example 1, and the battery cycle performance is significantly reduced, and the first effect of formation and fractional capacity are also significantly reduced. The lithium supplement additive in the positive electrode sheet of Comparative Example 2 has not been coated, and has poor stability, resulting in a low first effect of the battery, reduced capacity, and significantly reduced cycle performance. The positive electrode lithium supplement additive of Comparative Example 3 is not layered and coated, but lithium carbonate, the first coating material and the second coating material are blended and then calcined; the positive electrode lithium supplement additive of Comparative Example 4 is not coated with a second layer, and the first effect of formation, fractional capacity and battery cycle performance of the battery are significantly reduced.

[0169] In addition, Example 4 increases the dosage of the positive electrode lithium supplement additive, resulting in low battery first efficiency and capacity. The reason is that the positive electrode lithium supplement additive occupies part of the capacity in the negative electrode, forming part of the irreversible lithium insertion at the negative terminal, and the actual capacity of the positive terminal of the battery is not brought into play. Example 5 reduces the content of the positive electrode lithium supplement additive, resulting in low battery capacity and general cycle performance. The reason is that the dosage of the positive electrode lithium supplement additive is insufficient, and part of the positive electrode of the battery still forms irreversible lithium insertion in the negative electrode. Example 6 adds a large amount of positive electrode lithium supplement additive to the positive electrode, resulting in low battery first efficiency, reduced capacity, and reduced cycle performance. Example 7 uses lithium carbonate with different average pore size and porosity, Example 8 reduces the calcination temperature during the first layer of coating, Example 9 increases the dosage of the second coating material alumina, Example 10 changes the type of the second coating material, and Example 11 increases the calcination temperature during the second layer of coating. Compared with Example 1, the battery's first formation efficiency and battery cycle performance are both reduced. This shows that when the amount of the positive electrode lithium replenishing additive, the average pore size and porosity of the first coating material lithium carbonate when preparing the positive electrode lithium replenishing additive, the type and amount of the second coating material, and the calcination temperature during the first layer coating and the second layer coating meet the preferred conditions, the battery's first formation efficiency, volumetric capacity and battery cycle performance can be further improved.

[0170] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A positive electrode lithium supplement additive, characterized in that: The positive electrode lithium supplement additive comprises: a lithium-containing compound, and a first coating layer and a second coating layer sequentially coated on the surface of the lithium-containing compound; wherein, The first coating layer includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide and lithium lanthanum titanium oxide; The second cladding layer includes at least one of a Ga-containing compound, an Sm-containing compound, an Si-containing compound, an Al-containing compound, a V-containing compound, a Nb-containing compound, a Mg-containing compound, a Zr-containing compound, and a Zn-containing compound.

2. The positive electrode lithium supplement additive according to claim 1, characterized in that: Based on the total weight of the positive electrode lithium supplement additive, in the positive electrode lithium supplement additive, the contents of the lithium-containing compound, the first coating layer and the second coating layer are 80-99.8wt%, 0.01-20wt% and 0.01-20wt% respectively.

3. The positive electrode lithium supplement additive according to claim 1 or 2, characterized in that: The lithium-containing compound is selected from at least one of lithium acetate, lithium carbonate, lithium hydroxide and lithium nitrate, preferably lithium carbonate.

4. The positive electrode lithium supplement additive according to any one of claims 1 to 3, characterized in that: The second coating layer is an Al-containing compound; Preferably, the Al-containing compound is selected from at least one of aluminum oxide, aluminum hydroxide and aluminum carbonate, preferably aluminum oxide.

5. A method for preparing a positive electrode lithium supplement additive, characterized in that: The preparation method comprises the following steps: S1, performing a first mixing of the lithium-containing compound and the first coating material, and then performing a first calcination of the material obtained by the first mixing to obtain a first coating precursor; S2, performing a second mixing of the first coating precursor and the second coating material, and then performing a second calcination of the material obtained by the second mixing; wherein, The first coating material includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide and lithium lanthanum titanium oxide; The second coating material includes at least one of a Ga-containing compound, an Sm-containing compound, a Si-containing compound, an Al-containing compound, a V-containing compound, a Nb-containing compound, a Mg-containing compound, a Zr-containing compound, and a Zn-containing compound.

6. The preparation method according to claim 5, characterized in that: In S1, the lithium-containing compound and the first coating material are first mixed in a weight ratio of 1:(0.0001-0.25); Preferably, the first mixing is performed in the presence of a first solvent; Preferably, the first solvent is selected from C1-C4 monohydric alcohols, preferably ethanol; Preferably, based on the total weight of the lithium-containing compound and the first coating material being 1 g, the amount of the first solvent used is 0.5-20 mL; Preferably, the temperature of the first calcination is 400-1000° C., and the time is 60-900 min.

7. The preparation method according to claim 5 or 6, characterized in that: In S2, the first coating precursor and the second coating material are mixed in a weight ratio of 100:(0.01-25); Preferably, the second mixing is performed in the presence of a second solvent; and / or, the second mixing is performed at 30-80° C.; Preferably, the second solvent is selected from C1-C4 monohydric alcohols, preferably at least one of ethanol, methanol and isopropanol; Preferably, based on the total weight of the first coating precursor and the second coating material being 1 g, the amount of the second solvent used is 0.5-20 mL; Preferably, the second calcination is carried out at a temperature of 400-700° C. and for a time of 200-480 min.

8. A positive electrode lithium supplement additive prepared by the preparation method according to any one of claims 5 to 7.

9. A positive electrode sheet, characterized in that: The positive electrode sheet is obtained by coating a positive electrode slurry on the surface of a positive electrode current collector; wherein the positive electrode slurry comprises the positive electrode lithium supplement additive according to any one of claims 1-4 and 8.

10. A lithium ion battery, characterized in that: The battery comprises the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Pre-lithiation material, preparation method thereof and lithium battery

    CN109817926A

  • Lithium supplement additive and preparation method and application thereof

    CN115188957A

  • Lithium supplement material and preparation method thereof, positive electrode and secondary battery

    CN116525976A

  • Lithium supplement agent and preparation method thereof, positive pole piece and secondary battery

    CN116885187A

  • Positive electrode lithium supplementing additive, preparation method therefor and application thereof

    WO2023116512A1

Cited By

  • Composite sodium supplementing agent, preparation method thereof and sodium ion battery positive pole piece

    CN121076137A

  • Lithium ion battery additive and preparation method thereof, positive electrode slurry, positive electrode plate and lithium battery

    CN122025644A

  • A lithium-ion battery additive and its preparation method, positive electrode slurry, positive electrode sheet and lithium battery

    CN122025644B